Analisis Struktur dan Kemunculan Tingkat Kognitif pada Desain Kegiatan Laboratorium Materi Fotosintesis - Wahidah, Nur Sopiah; Supriatno, Bambang; Kusumastuti, Mimin Nurjhani (Assimilation: Indonesian Journal of Biology Education, 2018)
In practical activities usually teachers provide guidance in the form of students’ worksheet or design of laboratory activity. Based on field studies Supriatno (2009), only 24% design laboratory that can be done with the appropriate procedures and complete results in terms of data analysis and conclusion, so it does not support the construction of knowledge. It required the analysis to determine whether design laboratory used already support the construction of knowledge. Design laboratory analysis refers to the Vee diagram and revised Bloom's taxonomy as both lead students to construct knowledge. This research is a descriptive study with purposive sampling technique. The research data captured with a rare test work results table, the table where the component diagram Vee, Vee diagrams scoring table, as well as the revised Bloom's taxonomy table. The results of the 16 samples and 5 samples design laboratory, junior high school design laboratory of photosynthetic material shows that there are still procedural mistakes and instruction unstructured. Vee diagram component analysis results show the general components that arises is the question of focus, the object/event, theories, principles, concepts and knowledge claims. Components that are generally not appear that notes/transformation. Results of the analysis showed scores of each component Vee diagram, Vee diagram on middle and high school degign laboratory generally have not yet reached the ideal score. Results of the analysis showed the emergence of the cognitive level of cognitive level generally required design laboratory in middle and high school, namely C1, C2 and C3, with dominant category procedural C3. This cognitive level is in conformity with the demands of basic competencies middle school, but not in accordance with the demands of basic competencies of high school.